Suwardi Suryaningrat's Version of the Song L'internationale Based on History, Song Interpretation, and Song Structure - Yuwono, Ardi Tri; Sebastian, Andi; Clumpers, Pieter-Jan (Titian: Jurnal Ilmu Humaniora, 2024)
L'internationale is a poem written by Eugène Edine Pottier in 1873. In 1888, the poem was converted into a song by Pierre Chrétien De Geyter and since then L'internationale has been rendered into multiple languages globally, including Indonesian. Suwardi Suryaningrat translated the song L'internationale into Indonesian in 1920. This study aims to find out Suwardi Suryaningrat's cause for translated the song into Indonesian as well as the interpretation and analysis of Suwardi Suryaningrat's version of the L'internationale song. The methods used in this study are musicological analysis and historical methods with a qualitative approach. Suwardi Suryaningrat's reason for translating the song L'internationale into Indonesian is related to his habit of writing and translating foreign languages into Indonesian. The song L'internationale version of Suwardi Suryaningrat conveys a message about liberation from oppression carried out by the colonizers. The song consists of three parts that are organized by following a strophic pattern and a 4/4-time signature.